WITHDRAWN Complex impedance analysis of soft chemical synthesized NZCF systems - Parajuli, D.; Kumar Vagolu, Venkata; Chandramoli, K.; Murali, N.; Raj Sharma, Bhumi; Lal Shah, Nunu; Samatha, K. (Himalayan Physics, 2023)
This article was withdrawn on 28th April 2025. The withdrawal was carried out at the request of the journal’s editor and the corresponding author.